2015
DOI: 10.1007/s00276-015-1510-z
|View full text |Cite
|
Sign up to set email alerts
|

Visualization techniques of the inferior alveolar nerve (IAN): a narrative review

Abstract: PurposeThe purpose of this study was to produce an overview of the present visualization techniques of the inferior alveolar nerve (IAN) in order to reduce the rates of nerve damage after third molar (M3) removal and bilateral sagittal split osteotomy (BSSO).MethodsAn electronic literature search was performed of the English-language scientific literature published prior to December 31, 2014 using the LIMO KU Leuven search platform. Information on the specifications of the different imaging techniques, their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 44 publications
1
24
1
1
Order By: Relevance
“…[7][8][9] While on the other hand, the IAN was evaluated quantitatively using DTI and was visualized three-dimensionally by tractography in the present study. DTI can provide quantitative data based on the diffusivity and anisotropy of microscopic water motion within nerve fibres, and the nerve fibres can be visualized three-dimensionally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] While on the other hand, the IAN was evaluated quantitatively using DTI and was visualized three-dimensionally by tractography in the present study. DTI can provide quantitative data based on the diffusivity and anisotropy of microscopic water motion within nerve fibres, and the nerve fibres can be visualized three-dimensionally.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have evaluated the mandibular canal using MRI. [7][8][9] Among these, some researchers reported that changes to the neurovascular bundle including IAN could be evaluated on the basis of T 1 -and T 2 -related signal intensities on high-quality MR images.…”
Section: Introductionmentioning
confidence: 99%
“…CBCT is widely accepted to be the imaging method of choice for obtaining this information [ 1 , 2 ]. However, it is well known that the mandibular canal cannot usually be identified over its entire course even when CBCT is used.…”
Section: Discussionmentioning
confidence: 99%
“…The location of the mandibular canal must be correctly identified prior to dental implant surgery to avoid complications including intraoperative and postoperative hemorrhage and neurosensory loss. Cone beam computed tomography (CBCT) is considered the imaging modality of choice for this purpose [ 1 , 2 ] and is widely used for dental implant treatment planning. Several studies have evaluated the visibility of the mandibular canal on CBCT images [ 3 – 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Hence, the studies of prevalence and incidence of agenesis of third molars have been carried out on different population groups by various authors. [6][7][8] Unfortunately, data relating to these are available from only negligible reports from Nepal.…”
Section: Introductionmentioning
confidence: 99%